Rol del trabajador social frente a inmigrantes venezolanos en situación de calle en la provincia de El Oro año 2019 - Pando Nieves, Lidia Valeria (My University, 2021)
The present essay aims to analyze the role played by the Social Worker in the face of Venezuelan immigrants living on the streets in the province of El Oro in 2019. Migratory processes are inherent to the human species and to every living being, since all at a specific time move from place to place in search of better opportunities or for survival. That is why immigration is a latent social effect, since leaving your country of origin to settle in another involves social and economic factors, these can be due to natural disasters, wars, percussions or human rights violations. The phenomenon to be studied is Venezuelan immigration and the situation that is exposed every day in the streets. Social Work is a humanistic discipline focused on social change, promoting development and fighting for social equality, with principles of social justice, human rights, collective responsibility and respect for diversity are fundamental to social work INTERNATIONAL FEDERATION OF SOCIAL WORKERS FITS, 2014.
El presente ensayo tiene como objetivo Analizar el rol que desempeña el Trabajador Social frente a inmigrantes venezolanos en situación de calle en la provincia de El Oro año 2019. Los procesos migratorios son inherentes a la especie humana y a todo ser vivo, puesto que todos en un momento específico se trasladan de lugar en busca de mejores oportunidades o por supervivencia. Es por ello que la inmigración es un efecto social latente, ya que salir de su país de origen para radicarse en otro involucra factores sociales y económicos estos pueden ser por desastres naturales, guerras, percusiones o violaciones de los derechos humanos. El fenómeno a estudiar es la inmigración venezolana y la situación que se exponen día a día en las calles. El Trabajo Social es una disciplina humanista enfocada al cambio social, promueve el desarrollo y lucha por la igualdad social, con principios de justicia social, derechos humanos, responsabilidad colectiva y respeto a la diversidad son fundamentales para el trabajo social FEDERACIÓN INTERNACIONAL DE TRABAJADORES SOCIALES FITS,2014.
Keywords: INMIGRACION; TRABAJO SOCIAL; VULNERABILIDAD; ESTADO